miR-103/miR-195/miR-15b Regulate SALL4 and Inhibit Proliferation and Migration in Glioma - Li-Ping Chen (Molecules, 2018)
Glioma is the common highly malignant primary brain tumor. However, the molecular pathways that result in the pathogenesis of glioma remain elusive. In this study, we found that microRNA-103 (miR-103), microRNA-195 (miR-195), or microRNA-15b (miR-15b), which all have the same 5′ “seed„ miRNA portion and share common binding sites in the SALL4 3′-untranslated region (UTR), were downregulated in glioma tissues and cell lines. These miRNAs suppressed glioma cell proliferation, migration, and invasion, induced cell apoptosis, and decreased the level of the SALL4 protein, but not that of SALL4 mRNA, which was identified as a direct target of all three miRNAs. The caspase-3/7 activity expression in U251 cells overexpressing these miRNAs was rescued during SALL4 upregulation. An obvious inverse correlation was observed between SALL4 and miR-103 or miR-195 expression levels in clinical glioma samples. Moreover, enforced expression of SALL4 stimulated cell proliferation, migration, and invasion. In conclusion, these data suggest that miR-103, miR-195, and miR-15b post-transcriptionally downregulated the expression of SALL4 and suppressed glioma cell growth, migration, and invasion, and increased cell apoptosis. These results provide a potential therapeutic target that may downregulate SALL4 in glioma.